EFFECT OF INDUCED BIOLOGICAL FERMENTATIONS ON COFFEE SENSORY QUALITY - Cândido, Talita Amparo Tranches; Sepini, Pedro Pereira; Abrão, Polyana de Faria Cardoso; Oliveira, Reginaldo de; Campos, Kátia Alves; Paiva, Leandro Carlos (Coffee Science - ISSN 1984-3909, 2019)
Quality coffee consumption has been gradually increasing and having an impact on coffee prices not only for domestic but also for the foreign market. Different processing (preparation) methods of coffee will directly influence the quality of the final product. Taking this into consideration, this study aimed at evaluating sensory attributes of coffee submitted to biological fermentation. The experiment was carried out in a block design with 4 x 4 +1 factorial scheme. We evaluated the sensory attributes of coffee submitted to different fermentation treatments and times (8, 16, 24, 32 hours submerged in water, water + Saccharomyces cerevisiae, water + Saccharomyces bayanus, and water + Lactococcus lactis).